Co-Movement and Integration among Stock Markets: A Study of 10 Countries - Nitesh S Vibhute; Jeelan Basha V; Haralayya Bhadrappa (Journal of Advanced Research in Accounting and Finance Management, 2022)
A transparent market is important for economic growth of a country as it fosters investors’ confidence that will induce them to invest their savings, which in turn, will be used for productive purposes. Over the years, the reforms in the financial markets of Asia, Latin America, Europe and Africa have introduced different policies in order to erect a solid regulatory architecture for financial markets. Furthermore, it is observed that these policy initiatives have eased to liberalize various segments of financial markets so as to attract investors both foreign and domestic. By and large JKSE as the only indice has more than 10% average rate of return. However BSE is the most consistent index and hence it is more preference.